Sex‐specific fitness effects of unpredictable early life conditions are associated with DNA methylation in the avian glucocorticoid receptor. Issue 8 (20th January 2016) - Rubenstein, Dustin R.; Skolnik, Hannah; Berrio, Alejandro; Champagne, Frances A.; Phelps, Steven; Solomon, Joseph
Abstract: Organisms can adapt to variable environments by using environmental cues to modulate developmental gene expression. In principle, maternal influences can adaptively adjust offspring phenotype when early life and adult environments match, but they may be maladaptive when future environments are not predictable. One of the best‐studied 'maternal effects' is through modification of the offspring's hypothalamic–pituitary–adrenal (HPA) axis, the neuroendocrine system that controls responses to stress. In addition to the direct transfer of glucocorticoids from mother to offspring, offspring HPA function and other phenotypes can also be affected by epigenetic modifications like DNA methylation of the glucocorticoid receptor promoter. Here we examine how among‐year variation in rainfall is related to DNA methylation during development and fitness in adulthood in the superb starling ( Lamprotornis superbus), which lives in a climatically unpredictable environment where early life and adult environments are unlikely to match. We found that DNA methylation in the putative promoter of the glucocorticoid receptor gene is reduced in chicks – particularly in males – born following drier prebreeding periods. Additionally, DNA methylation is lower in males that become breeders than those that never breed. However, there is no relationship in females between DNA methylation and the likelihood of dispersing from the natal group to breed elsewhere. These results suggest that early life conditions may positively affect fitness in a sex‐specific manner through chemical modification of an HPA‐associated gene. This study is the first to show that epigenetic modifications during early life may influence the fitness of free‐living organisms adapted to unpredictable environments.